Načrtovanje izdelovalnih sistemov, podprto s simulacijo - Perme, Tomaž (Strojniški vestnik, 2003)
The increasing complexity of modern manufacturing systems calls for computer-aided planning tools, which can help planners better use their knowledge, experience, creativity and intuition. Only by means of a simulation, which is a significant part of this tools, can the "real" properties of a manufacturing or assembly system be obtained during the planing phase. The main parts of this paper describe the development of a simulation package (LASIMCO) for the computer-aided planning of manufacturing and assembly systems, as well as the use of this tool in a case study.
Keywords: sistemi proizvodni; planiranje računalniško podprto; proizvodnja navidezna; mreže Petri; proizvodni sistemi; modeliranje; simulacija; Petrijeve mreže